Determination of EBV genotypes and EBNA1 oncogene variants among breast cancer patients in Peshawar, Pakistan - Khattak, Ayesha; Khan, Sanaullah; Nauman, Fatima; Sabeen, Itrat; Khan, Muhammad Bar (International Journal of Pathology, 2025)
Background: Epstein-Barr virus (EBV) is a common DNA virus linked to several human cancers, including breast cancer (BC). Specific EBV oncogenes, like EBNA1, are also implicated in the process of oncogenesis. This study aimed to investigate the prevalence of different EBV genotypes and EBNA1 oncogene variants in BC patients in Peshawar, Pakistan.Methodology: This study was conducted in the Institute of zoological sciences, University of Peshawar, Khyber Pakhtunkhwa.  Tumor biopsies and demographic data were collected from 75 BC patients. DNA was extracted from the samples and EBV genotypes were detected using polymerase chain reaction (PCR) with specific primers. The EBNA1 oncogene was also amplified via PCR and sequenced using Sanger's sequencing method. The resulting sequences were analyzed to determine EBNA1 variants. All data were analyzed using descriptive statistics, primarily percentages and chi square test where applicable.Results: EBV was detected in 40% of the study participants. All positive samples were identified as EBV genotype-1. The most prevalent EBNA1 type found in these patients was the prototype P-Threonine. The study population was predominantly post-menopausal (63%), with most tumors being malignant (93%) and of grade II (69%). Among the malignant cases, 63% were hormone receptor (HR) positive, 11% were HER2-positive, and 26% were triple-negative breast cancer (TNBC).Conclusion: EBV type-1 and EBNA1 P-Threonine are present in breast cancer patients in Peshawar, Pakistan. This study provides valuable insight into the molecular characteristics of EBV in breast cancer within this specific population